The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1039/c8tb02425a
|View full text |Cite
|
Sign up to set email alerts
|

Improved antibacterial properties of collagen I/hyaluronic acid/quaternized chitosan multilayer modified titanium coatings with both contact-killing and release-killing functions

Abstract: The HACC-based multilayer could inhibit the colonization of bacteria via contact-killing and release-killing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
38
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 61 publications
(41 citation statements)
references
References 40 publications
2
38
0
Order By: Relevance
“…It is implied that the additional CGA delayed increasing pH value of the samples. Simultaneously, chitosan coating was observed to be effective in suppressing product degradation during storage, which is in accordance with the earlier studies(Ao et al, 2019;Li, Wu,…”
supporting
confidence: 91%
See 2 more Smart Citations
“…It is implied that the additional CGA delayed increasing pH value of the samples. Simultaneously, chitosan coating was observed to be effective in suppressing product degradation during storage, which is in accordance with the earlier studies(Ao et al, 2019;Li, Wu,…”
supporting
confidence: 91%
“…It has been reported that lipid oxidization in chitosan‐coated products impede by the chitosan macromolecules (Ao et al, ; Hassannejad et al, ; Pawlik et al, ), while slow release of CGA from edible coating also retards lipid oxidization(Jiao et al, ; Liu & Park, ). It can be seen from Table that higher concentration of CGA resulted in lowest TBARS values during storage.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…[27] Haiyong Ao et al used the LbL selfassembly process of collagen type I/hyaluronic acid/quaternary ammonium salt of chitosan to improve the antibacterial properties of titanium coating. [28] Barman et al also studied the antibacterial activity of two segmented amphiphilic PUs, containing a primary or secondary amine group, against Escherichia coli bacteria. [29] In the current research, the surface of the synthesized PU film was activated using nitrogen gas low-pressure plasma treatment and grafted with poly(acrylic acid).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, it is critical to establish a strong biological epithelial sealing at the implant surface in the cervical region to prevent peri-implantitis and increase the survival rate of dental implants. Surface modifications, such as fabrication of a biomimetic antibacterial multilayer coating to prevent implant infection (Ao et al, 2019), implant surface modification with protease activated receptor 4-activating peptide to prevent bacterial attachment and invasion (Maeno et al, 2017), and functionalization with superparamagnetic TiO2 coatings to prevent soft tissue recession and inflammatory reaction (Li et al, 2019), have been widely studied in the area of dental implant materials in recent years. However, no surface modification strategy to date has been able to create a perfect biological sealing structure around the transmucosal implant.…”
Section: Introductionmentioning
confidence: 99%